2012
DOI: 10.1242/dev.075242
|View full text |Cite
|
Sign up to set email alerts
|

Hh signalling is essential for somatic stem cell maintenance in theDrosophilatestis niche

Abstract: In the Drosophila testis, germline stem cells (GSCs) and somatic cyst stem cells (CySCs) are arranged around a group of postmitotic somatic cells, termed the hub, which produce a variety of growth factors contributing to the niche microenvironment that regulates both stem cell pools. Here we show that CySC but not GSC maintenance requires Hedgehog (Hh) signalling in addition to Jak/Stat pathway activation. CySC clones unable to transduce the Hh signal are lost by differentiation, whereas pathway overactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
70
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 47 publications
9
70
0
Order By: Relevance
“…In addition, Smo 3 and Ptc IIW null alleles were used to inactivate and activate Hh signaling, respectively, in mosaic analysis with a repressible cell marker (MARCM). The results showed that Smo 3 mutant CySCs disappeared rapidly, while Ptc IIW mutant CySCs were found in all testes (Supplementary information, Table S1, Figures S4 and S5), which is consistent with the recent findings by others [7].…”
Section: -Positive Cells Under Different Hh Signaling Activities (Susupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, Smo 3 and Ptc IIW null alleles were used to inactivate and activate Hh signaling, respectively, in mosaic analysis with a repressible cell marker (MARCM). The results showed that Smo 3 mutant CySCs disappeared rapidly, while Ptc IIW mutant CySCs were found in all testes (Supplementary information, Table S1, Figures S4 and S5), which is consistent with the recent findings by others [7].…”
Section: -Positive Cells Under Different Hh Signaling Activities (Susupporting
confidence: 91%
“…Our study identified that Hh signaling activity mainly acts in CySCs and is critical for CySC maintenance in Drosophila testis, which further confirmed an independent finding published recently [7]. In addition, we revealed three novel aspects of Hh signaling in the testis ( Figure 1Y).…”
Section: -Positive Cells Under Different Hh Signaling Activities (Susupporting
confidence: 91%
See 1 more Smart Citation
“…1A). Several signaling pathways have been reported to regulate CySCs, including the JAK-STAT pathway (Issigonis et al, 2009;Kiger et al, 2001;Leatherman and DiNardo, 2010;Singh et al, 2010;Tulina and Matunis, 2001), the EGFR pathway (Eun et al, 2014;Kiger et al, 2000;Tran et al, 2000), the Hpo pathway (Amoyel et al, 2014) and the Hh pathway (Amoyel et al, 2013;Michel et al, 2012;Zhang et al, 2013b). Although these pathways govern stem cell behavior, the function of PTMs during this process is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The hub secretes the JAK-STAT ligand Unpaired (Upd), Hedgehog (Hh) and bone morphogenetic proteins (BMPs) to regulate stem cell maintenance and repress differentiation in both GSCs and CySCs (de Cuevas and Matunis, 2011). Hub-derived Hh is required in CySCs for self-renewal independently of JAK-STAT signalling (Amoyel et al, 2013;Michel et al, 2012). Additionally, somagermline communication mediated by the epidermal growth factor receptor (EGFR) pathway is required during and after encapsulation (Hudson et al, 2013;Sarkar et al, 2007;Schulz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%